The modern law of contract - Stone, Richard 1951-; Devenney, James (London Routledge Taylor & Francis Group, c2017., 2017)
The "Modern Law of Contract" is a clear and logical textbook, written by an experienced author team with well over 50 years' teaching and examining experience.

Fully updated to address the Consumer Rights Act 2015 and recent key cases in Contract Law, it offers a carefully tailored overview of all key topics for LLB and GDL courses. The book also includes a number of learning features designed to enhance comprehension and aid to exam preparation, allowing reader to:
1. understand and remember core topics
2. identify important cases and assess their relevance
3. reflect on how contract law operates in context
4. consolidate learning and prepare for assessment
First edition published by Cavendish 2002
Eleventh edition published by Routledge 2015
Includes bibliographical and index
Keywords: Contracts -- England